Photoionization of isomeric molecules: from the weak-field to the strong-field limit - Zigo, Stefan John (Kansas State University, 2017)
Ultra-fast spectroscopy has become a common tool for understanding the structure and dynamics of atoms and molecules, as evidenced by the award of the 1999 Nobel Prize in Chemistry to Ahmed H. Zewail for his pioneering work in femtochemistry. The use of shorter and more energetic laser pulses have given rise to high intensity table-top light sources in the visible and infrared which have pushed spectroscopic measurements of atomic and molecular systems into the strong-field limit. Within this limit, there are unique phenomena that are still not well understood. Many of such phenomena involve a photoionization step. For three decades, there has been a steady investigation of the single ionization of atomic systems in the strong-field regime both experimentally and theoretically. The investigation of the ionization of more complex molecular systems is of great interest presently and will help with the understanding of ultra-fast spectroscopy as a whole. In this thesis, we explore the single ionization of molecules in the presence of a strong electric field. In particular, we study molecular isomer pairs, molecules that are the same elementally, but different structurally. The main goal of this work is to compare the ionization yields of these similar molecular pairs as a function of intensity and gain some insight into what differences caused by their structure contribute to how they ionize in the strong-field limit. Through our studies we explore a wavelength dependence of the photoionization yield in order to move from the multi-photon regime of ionization to the tunneling regime with increasing wavelength. Also, in contrast to our strong-field studies, we investigate isomeric molecules in the weak-field limit through single photon absorption by measuring the total ionization yield as a function of photon energy. Our findings shed light on the complexities of photoionization in both the strong- and weak-field limits and will serve as examples for the continued understanding of single ionization both experimentally and theoretically.
Keywords: Strong-field ionization; Ultrafast spectroscopy; Isomers; Weak-field ionization; Femtosecond lasers; Time-of-flight mass spectroscopy